Konsep Pembelajaran ( Back to Al-Qur’an) - Fatonah, Isti (Institut Agama Islam Negeri (IAIN) Metro, 2014)
Indonesian education is essentially form a complete human beings who believe, knowledgeable and charity. To achieve these objectives, in general, the Qur'an can be used as guidance. Lifelong education motto of life long education and education for all and all for education should be a principle of life. Learning is part of worship. Qur'an clues that describe methods of education and learning that can touch the mind and soul of learners. Lifelong education motto of life long education and education for all and all for education should be a principle of life.